2015
DOI: 10.1016/j.jmmm.2014.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic AC susceptibility imaging (sASI) of magnetic nanoparticles

Abstract: This study demonstrates a method for alternating current (AC) susceptibility imaging (ASI) of magnetic nanoparticles (mNPs) using low cost instrumentation. The ASI method uses AC magnetic susceptibility measurement to create tomographic images using an array of drive coils, compensation coils and fluxgate magnetometers. Using a spectroscopic approach in conjunction with ASI, a series of tomographic images can be created for each frequency measurement and is termed sASI. The advantage of sASI is that mNPs can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 54 publications
1
6
0
Order By: Relevance
“…In a previous study we confirmed that our experimental apparatus is able to distinguish between different sized MNPs through spectroscopic measurement [43]. Spectroscopic measurement was accomplished by placing each sample in the test holder (Fig 1) and multiplexing through each frequency for 5 s. Prior to the measurement of a sample, a background measurement was also taken.…”
Section: Methodssupporting
confidence: 62%
“…In a previous study we confirmed that our experimental apparatus is able to distinguish between different sized MNPs through spectroscopic measurement [43]. Spectroscopic measurement was accomplished by placing each sample in the test holder (Fig 1) and multiplexing through each frequency for 5 s. Prior to the measurement of a sample, a background measurement was also taken.…”
Section: Methodssupporting
confidence: 62%
“…Another type of MNP imaging technique can be categorized into Magnetic Susceptibility Imaging (MSI) [ 22 ], one of which is called Susceptibility Magnitude Imaging (SMI) [ 23 ]. This technique was further developed using nonlinear MNP responses by spectroscopy AC susceptibility Imaging (sASI) [ 24 ] and nonlinear Susceptibility Magnitude Imaging (nSMI) [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…Note that the effective relaxation time Ï„ eff is determined as the maximum in the imaginary part ωτ eff = 1. Similar to MRXI, additional spatial encoding in ACS by multiple sensors or excitation coils allows for the development of MNP imaging approaches [33][34][35][36].…”
Section: Mnp Response To Alternating Magnetic Fieldsmentioning
confidence: 99%